Environmental Stress Testing of Wafer-Level Au-Au Thermocompression Bonds Realized at Low Temperature: Strength and Hermeticity. (29th April 2015) - Malik, N.; Tofteberg, H. R.; Poppe, E.; Finstad, T. G.; Schjølberg-Henriksen, K.
Abstract : Hermeticity, reliability and strength of four laminates bonded at different temperatures by Au-Au thermocompression bonding have been investigated. Laminates with a diameter of 150 mm were realized by bonding a wafer containing membrane structures to a Si wafer with patterned bond frames. A bond tool pressure of 2266 mbar was applied for 15 minutes at temperatures ranging from 150–300°C. The hermetic properties were estimated by membrane deflection measurements applying white-light interferometry after bonding. Reliability was tested by exposing the laminates to a steady-state life test, a thermal shock test, and a moisture resistance test. Bond strength was estimated by pull test measurements. A dicing yield above 90% was obtained for all laminates. Laminates bonded at 200°C and above had significantly higher hermetic yield than the laminate bonded at 150°C. No degradation in hermeticity was observed after the reliability tests. The maximum leakage rate (MLR) was estimated from two measurements of membrane deflection executed at two different times and was below 10 −11 mbar ⋅ l ⋅ s −1 . The average bond strength ranged from 44 to 175 MPa.